2023
DOI: 10.3390/agriculture13010198
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Mechanical/Physical Pretreatments with Trypsin or Pancreatin on Arthrospira platensis Protein Degradation

Abstract: Arthrospira platensis contains high protein content and quality, which makes it a promising feed source for livestock animals. However, this microalga presents a recalcitrant peptidoglycan cell wall, and its main proteins form protein-pigment complexes attached to the algal thylakoid membrane. The purpose of the present study was to evaluate the effect of mechanical/physical pretreatments (bead milling, extrusion, freeze-drying, heating, microwave and sonication) combined with commercial enzymes (trypsin or pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Recent in vitro studies have provided additional clarity on the enzymatic hydrolysis of A. platensis proteins following extrusion. The research by Costa et al [ 17 ] has been particularly informative, demonstrating an enhanced breakdown of protein fractions within the 18 to 26 kDa range, identified as phycocyanin subunits [ 16 ], when extruded A. platensis is combined with commercial pancreatin. This finding is pivotal as it indicates that extrusion pre-treatment can lead to a more efficient enzymatic release of phycocyanin, a protein known for its nutritional and functional benefits.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent in vitro studies have provided additional clarity on the enzymatic hydrolysis of A. platensis proteins following extrusion. The research by Costa et al [ 17 ] has been particularly informative, demonstrating an enhanced breakdown of protein fractions within the 18 to 26 kDa range, identified as phycocyanin subunits [ 16 ], when extruded A. platensis is combined with commercial pancreatin. This finding is pivotal as it indicates that extrusion pre-treatment can lead to a more efficient enzymatic release of phycocyanin, a protein known for its nutritional and functional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…However, a conundrum arises from these studies where extrusion, despite its benefits, also causes protein denaturation and aggregation. Costa et al [ 17 ] and Spínola et al [ 18 ] observed that these denatured proteins were often not detectable in the supernatant post-extrusion, suggesting a profound modification of their physical state. Such changes are attributed to the harsh conditions of high pressure and temperature inherent to the extrusion process, as documented in the structural studies of proteins by Ahmed et al [ 37 ] and Buecker et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations